1991
DOI: 10.1523/jneurosci.11-08-02443.1991
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ganglioside GM1 with the B subunit of cholera toxin modulates growth and differentiation of neuroblastoma N18 cells

Abstract: The present study uses the B subunit of cholera toxin, a protein that binds specifically to ganglioside GM1, to examine the role of endogenous GM1 in the process of growth and differentiation of mouse neuroblastoma N18 cells. Binding of the B subunit to neuroblastoma N18 cells inhibited DNA synthesis with concomitant induction of differentiation. The B subunit induced pronounced morphological changes: an increase in neurite outgrowth with branched neurites and spinelike processes. The distinct morphological al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Earlier studies using CtxB application to rat lymphocytes (50) and Jurkat T cells (51) revealed Ca 2ϩ influx through an undefined channel while similar studies with neural cells showed CtxB-induced neurite outgrowth as a consequence of the Ca 2ϩ increase (33,52,53). The Ca 2ϩ channel was revealed to be voltage independent (33) and a recent report specified the channel type as TRPC5 (32), a member of the canonical subfamily belonging to the transient receptor potential superfamily of signal transductiongated ion channels (19).…”
Section: Discussionmentioning
confidence: 90%
“…Earlier studies using CtxB application to rat lymphocytes (50) and Jurkat T cells (51) revealed Ca 2ϩ influx through an undefined channel while similar studies with neural cells showed CtxB-induced neurite outgrowth as a consequence of the Ca 2ϩ increase (33,52,53). The Ca 2ϩ channel was revealed to be voltage independent (33) and a recent report specified the channel type as TRPC5 (32), a member of the canonical subfamily belonging to the transient receptor potential superfamily of signal transductiongated ion channels (19).…”
Section: Discussionmentioning
confidence: 90%
“…Recent reports provide evidence that cholera toxin inhibits dendritic cell differentiation by cAMP-mediated inhibition of IRF8 function [25] . It was also documented that ganglioside GM1 reaction with B subunit of cholera toxin induces neuron-like differentiation of PC12 and neuroblastoma cells [26,27] . Therefore, it seems reasonable to postulate that GSK-3β might not be the unique molecular targets of cholera toxin that might contribute to the differentiation of human glioblastoma cells.…”
Section: Wwwchinapharcom LI Y Et Almentioning
confidence: 95%
“…Guerrant et al (15) reported that active whole cholera toxin, but not inactive choleragenoid, produces elevation of cAMP and parallel morphological changes in CHO cells. Ganglioside GM1 reaction with the B subunit of cholera toxin was reported to induce neuron-like differentiation of PC12 and neuroblastoma cells (16,17). All of the findings mentioned above revealed the potential of cholera toxin, a kind of biotoxin, in the differentiation induction of tumor cells.…”
mentioning
confidence: 89%